The Impeachment of Dilma Rousseff and the debate on Twitter - Chicarino, Tathiana Senne; Segurado, Rosemary; Araújo, Rafael de Paula Aguiar; Tavares, Luis Eduardo; Malina, Pedro; Lobo, Denis Carneiro (Aurora. Revista de Arte, Mídia e Política, 2018)
Empirically supported by Twitter activity, especially with regard to the profiles related to the city of São Paulo, this article presents an analysis of the main events in the year 2016 related to Dilma Rousseff’s impeachment proceedings. Based on data collected between March 5 and October 16, we adopted the Issue Mapping methodology, which seeks to map everyday narratives, relevant facts or events in the networked public sphere. Two organically articulated axes composes the textual structure. In addition, we offer a detailed explanation of the current political scenario along with the analysis of the Twitter information flow based on street demonstrations (pro and against), impeachment trial, and the 2016 Summer Olympics.